2016
DOI: 10.5454/mi.10.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Heterologous Expression of Extracellular Plantaricin F Produced by Lactobacillus plantarum S34 Isolated from “Bekasam” in Lactococcus lactis

Abstract: Submission ID: 1079439462File name: logous_Expression_of _Extracellular_Plantaricin_F_in_L.lactis.pdf (2.14M) Word count: 6759Character count: 35493

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Furthermore, 10 ng/ml nisin was applied to optimize the heterologous expression level. Previous studies reported the construction of bacteriocins from various origins (plantaricin E, F, and W), which were successfully expressed in L. lactis, generating mature form at transcription and translational level [19,41,42]. Another studies also reported that nisin concentration at 10 ng/ml enhanced protein expression level 4.59x of native HBcAg gene [20], and conversely codon-optimized HBcAg gene was reported to produce the highest expression level with 50 ng/ml nisin concentration [17].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 10 ng/ml nisin was applied to optimize the heterologous expression level. Previous studies reported the construction of bacteriocins from various origins (plantaricin E, F, and W), which were successfully expressed in L. lactis, generating mature form at transcription and translational level [19,41,42]. Another studies also reported that nisin concentration at 10 ng/ml enhanced protein expression level 4.59x of native HBcAg gene [20], and conversely codon-optimized HBcAg gene was reported to produce the highest expression level with 50 ng/ml nisin concentration [17].…”
Section: Discussionmentioning
confidence: 99%
“…In accordance to the results of Lages et al, 23 the administration of 10 ng/ml nisin induction in L. lactis increased gene expression, resulting in more protein than the non-induced. The concentrations of nisin has compared in the range between 0.5 and 5 ng/ml to induce the expression genes of antibacterial in L. lactis, and obtained the result that the highest of antibacterial was produced by L. lactis induced with nisin at 5 ng/ml by Mustopa et al 24 Moreover, codon optimization can also be performed. Nisin concentration required for induction is very low, between 0.5-10 ng/ml, while the high concentration of nisin of more than 10 ng/ml used will have negative effect on the host because it can suppress the growth of L. lactis.…”
Section: Discussionmentioning
confidence: 99%
“…The new L. plantarum EK11 strain analyzed in our study exhibits genetic predisposition for the production of three important bacteriocins (PlnG, PlnEF, and PlnA). The biosynthesis of plantaricin J (PlnJ) and plantaricin K is induced by the activity of plantaricin A (PlnA), which determines the proper functioning of the ABC transporter responsible for plantaricins transport outside the cell (Anderssen et al, 1998; Mustopa et al, 2016). This indicates a direct association between the number of genes involved in the biosynthesis of plantaricins in a bacterial strain and its bactericidal or bacteriostatic potential against specific pathogens (Rizello et al, 2014;).…”
Section: Detection Of Genes Encoding Selected Bacteriocinsmentioning
confidence: 99%